Carbon nanotube doped pericardial matrix derived electroconductive biohybrid hydrogel for cardiac tissue engineering - Roshanbinfar, Kaveh; Mohammadi, Zahra; Sheikh-Mahdi Mesgar, Abdorreza; Dehghan, Mohammad Mehdi; Oommen, Oommen P.; Hilborn, Jöns; Engel, Felix (Biomaterials Science, 2019)
Cardiovascular diseases represent a major socio-economic burden. In recent years, considerable effort has been invested in optimizing cell delivery strategies to advance cell transplantation therapies to restore heart function for example after an infarct. A particular issue is that the implantation of cells using a non-electroconductive matrix potentially causes arrhythmia. Here, we demonstrate that our hydrazide-functionalized nanotubes-pericardial matrix-derived electroconductive biohybrid hydrogel provides a suitable environment for maturation of human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. hiPSC-derived cardiomyocytes exhibited an improved contraction amplitude (>500%) on conductive hydrogels compared to cells cultured on Matrigel®. This was accompanied by increased cellular alignment, enhanced connexin 43 expression, and improved sarcomere organization suggesting maturation of the hiPSC-derived cardiomyocytes. Sarcomeric length of these cells increased from 1.3 to 1.7 μm. Moreover, 3D cell-laden engineered tissues exhibited enhanced calcium handling as well as positive response to external electrical and pharmaceutical stimulation. Collectively, our data indicate that our biohybrid hydrogels consisting of solubilized nanostructured pericardial matrix and electroconductive positively charged hydrazide-conjugated carbon nanotubes provide a promising material for stem cell-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-09-03